Negative Evidence for a Functional Role of Neuronal DNMT3a in Persistent Pain - Saunders, Jessica; Hore, Zoe; Gentry, Clive; McMahon, Stephen; Denk, Franziska (Frontiers in Molecular Neuroscience, 2018)
Traditionally, neuroscience has had to rely on mixed tissue analysis to examine transcriptional and epigenetic changes in the context of nervous system function or pathology. However, particularly when studying chronic pain conditions, this approach can be flawed, since it neglects to take into account the shifting contribution of different cell types across experimental conditions. Here, we demonstrate this using the example of DNA methyltransferases (DNMTs) – a group of epigenetic modifiers consisting of Dnmt1, Dnmt3a and Dnmt3b in mammalian cells. We used sensory neuron-specific knockout mice for Dnmt3a/3b as well as pharmacological blockade of Dnmt1 to study their role in nociception. In contrast to previous analyses on whole tissue, we find that Dnmt3a and 3b protein is not expressed in adult DRG neurons, that none of the DNA methyltransferases are regulated with injury and that interfering with their function has no effect on nociception. Our results therefore currently do not support a role for neuronal DNA methyltransferases in pain processing adult animals.